2021
DOI: 10.1002/cbdv.202100604
|View full text |Cite
|
Sign up to set email alerts
|

Cardamonin Presents in Vivo Activity against Schistosoma mansoni and Inhibits Potato Apyrase

Abstract: Schistosomiasis, a neglected tropical disease caused by Schistosoma species, harms over 250 million people in several countries. The treatment is achieved with only one drug, praziquantel. Cardamonin, a natural chalcone with in vitro schistosomicidal activity, has not been in vivo evaluated against Schistosoma. In this work, we evaluated the in vivo schistosomicidal activities of cardamonin against Schistosoma mansoni worms and conducted enzymatic apyrase inhibition assay, as well as molecular docking analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(114 reference statements)
1
12
0
Order By: Relevance
“…Many natural products have demonstrated anti-schistosomiasis activity [10,[50][51][52]. The aurone scaffold is another source of antimalarial compounds [53,54] that has been investigated for anti-schistosomiasis potential [55,56].…”
Section: Other Antimalarialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many natural products have demonstrated anti-schistosomiasis activity [10,[50][51][52]. The aurone scaffold is another source of antimalarial compounds [53,54] that has been investigated for anti-schistosomiasis potential [55,56].…”
Section: Other Antimalarialsmentioning
confidence: 99%
“…The latter of those, perhexiline maleate (62), is an anti-angina drug whose efficacy against schistosomiasis had been studied previously [86,87]. Starting from those three hits, pharmacophore Leads resulting from a large high-throughput screening experiment (51)(52)(53)(54)(55)(56)(57)(58)(59).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, previous studies have showed that the SmNTPDases isoforms have immune cross-reactivity with the potato ( Solanum tuberosum ) apyrase [ 9 , 10 , 11 ], sharing high homology and similarity in their active sites [ 9 , 10 , 11 , 12 ]. Regarding this, some natural compounds, such as cardamonin, have promoted the inhibition of both SmNTPDases and potato apyrase, also showing in vivo antischistosomal effects against S. mansoni [ 13 , 14 , 15 ]. Since its obtainment with high purity is easy, it has been proposed that potato apyrase may be used in the initial screening for selecting potential antischistosomal compounds with affinity for SmNTPDases in complex samples, such as plant extracts [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this, some natural compounds, such as cardamonin, have promoted the inhibition of both SmNTPDases and potato apyrase, also showing in vivo antischistosomal effects against S. mansoni [ 13 , 14 , 15 ]. Since its obtainment with high purity is easy, it has been proposed that potato apyrase may be used in the initial screening for selecting potential antischistosomal compounds with affinity for SmNTPDases in complex samples, such as plant extracts [ 13 , 15 ]. In this regard, in a preliminary assessment of some plant extracts against potato apyrase, the hydroalcoholic extract of Centella erecta (L.f.) Fern.…”
Section: Introductionmentioning
confidence: 99%